Web-Based Virtual Laboratory Design in Class XI Chemistry Subject - Dony Novaliendry; Rahmani, Asyifa; SriWahyuni, Titi; Fajri, Bayu Ramadhani (International Journal of Online and Biomedical Engineering (iJOE), 2023)
Practicum activities are crucial for supporting students’ success in the teaching and learning process. To conduct the practicum, several factors are required, which vary depending on the field of practice. Adequate facilities and equipment are also necessary. The purpose of this research is to develop a web-based interactive virtual learning application for chemistry lab experiments. The stages involved in creating an application using the multimedia development life cycle (MDLC) method include planning, designing, collecting material, manufacturing, testing, and distribution. Creating applications using Unity software and designing assets with Adobe Illustrator. Virtual labs can help overcome the lack of costs associated with procuring laboratory equipment and materials, reduce the risk of work accidents, and can be accessed from anywhere.